2017
DOI: 10.1111/jam.13605
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of rareActinobacteria, a new insight for finding natural products with antivascular calcification activity

Abstract: Aim: Vascular calcification (VC) is a significant pathological process in some life-threatening diseases. Several pathological mechanisms, including transdifferentiation of vascular smooth muscle cells to osteoblast-like cells and apoptosis are involved in VC. Compounds with an inhibitory effect on these processes are potentially efficient medications. In consideration of the multiple biological activities of Actinobacteria, this research was aimed at finding anti-VC metabolite-producing Actinobacteria. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In addition, this FBE showed good anti‐VC characteristics in the alizarin red staining and anti‐apoptotic effects in the VSMCs under the calcification condition (Salimi et al . ). Recent studies have indicated that hyperglycaemia induces VC in the human aortic smooth muscle cells by up‐regulation the osteoblastic markers (Giugliano et al .…”
Section: Resultsmentioning
confidence: 97%
“…In addition, this FBE showed good anti‐VC characteristics in the alizarin red staining and anti‐apoptotic effects in the VSMCs under the calcification condition (Salimi et al . ). Recent studies have indicated that hyperglycaemia induces VC in the human aortic smooth muscle cells by up‐regulation the osteoblastic markers (Giugliano et al .…”
Section: Resultsmentioning
confidence: 97%
“…The metabolic extracts were screened for toxicity against larvae of Artemia salina (brine shrimp) as described before (Salimi et al . ). The test was performed in triplicate with extract concentrations of 10, 50 and 100 μ g ml −1 and the lethal dose of extracts was calculated by enumeration of the dead larvae after 24 h.…”
Section: Methodsmentioning
confidence: 97%
“…), enzyme inhibitors (Imada ), antivascular calcification activity (Salimi et al . ), antitumour (Salcedo et al . ), anti‐angiogenic and proangiogenic agents (Azarakhsh et al .…”
Section: Introductionmentioning
confidence: 99%
“…ignorata is a rare human pathogen. However, soil samples have been described as a possible reservoir (2,7,8). Accordingly, this patient, who had frequent exposure to soil through his work as a gardener, might have acquired the infection from that source.…”
Section: S Ince the Description Of Nocardia Ignorata In 2001mentioning
confidence: 92%